THE EFFECT OF PROBLEM-BASED LEARNING ON STUDENTS’ SELF-CONFIDENCE IN ENGLISH LEARNING - Dewi Reski Yusria; Nur Islah Nanda Astarini (Universitas Negeri Makassar, 2026)
This research aims to analyze the effect of the Problem-Based Learning (PBL) model on students’ self-confidence at SMP Negeri 1 Eremerasa. The research method used is an experimental design with a pre-experimental approach, employing pre-tests and post-tests. The research sample consisted of 21 students from class VIII D. The instrument used to measure student learning motivation was a questionnaire consisting of 20 items with a Likert scale. Data analysis was conducted using descriptive statistics, including the calculation of mean and standard deviation, as well as a t-test to examine significant differences between pre-test and post-test results. Self-confidence is an important factor in successful English learning. Students with high self-confidence tend to ask questions, express opinions, and use English more actively in communication. This study aimed to examine the effect of Problem-Based Learning (PBL) on students’ self-confidence in English learning. The study involved 30 eighth-grade students using a pre-test and post-test design. The results showed that the average self-confidence score increased from 58.20 in the pre-test to 78.45 in the post-test. Statistical analysis indicated that the t-value of 7.12 was higher than the t-table value of 2.045 at the 0.05 significance level, indicating a significant improvement after the implementation of PBL.